ROI-based efficient video data processing for large-scale cloud storage in intelligent CCTV environment - hyeok Lee, Dong; je. Park, Nam (International Journal of Engineering and Technology, 2018)
Background/Objectives: Big data environment is being realized. Recently, intelligent public safety environment on the foundation of the image processing technique based on big data is being introduced, and accordingly, processing CCTV images is becoming more important day by day.Methods/Statistical analysis: In this paper, an efficient technique to send image information for mass cloud storage environment was proposed. With the offered method, only the ROI area is extracted and partial object images are transmitted, and it has the strengths of higher efficiency and protected privacy with the application of a masking technique.Findings: it is general to apply the masking technique partially to face information, and in this study, the privacy of the image data registered in the cloud storage was to be protected based on this masking technique, and an efficient data transmission structure grounded on ROI area extraction was proposed.Improvements/Applications: With the offered method, only the ROI area is extracted and partial object images are transmitted, and it has the strengths of higher efficiency and protected privacy with the application of a masking technique.Â Â